Preoperative computed tomography evaluation of the paranasal sinuses: what should the physician know? - pictorial essay - Ribeiro,Bruno Niemeyer de Freitas (2019)
Abstract The introduction of functional endoscopic sinus surgery in the 1980s brought about a drastic change in the treatment of patients with rhinosinusitis, improving quality of life through the removal of pathological processes or anatomical variations that obstruct the drainage pathways of the paranasal sinuses. However, despite the routine use of computed tomography in the anatomical evaluation of the paranasal sinuses, most radiological reports still do not provide sufficient information to guide the surgical planning. The objective of this pictorial essay was to demonstrate, through computed tomography, the main anatomical variations of the paranasal sinuses, the recognition of which is fundamental for preoperative planning, in order to avoid treatment failure and iatrogenic complications.